Effects of neurofeedback on the dysregulation profile in children with ADHD: SCP NF meets SDQ-DP - a retrospective analysis - Heinrich, Hartmut; Gevensleben, Holger; Becker, Andreas; Rothenberger, Aribert (Psychological Medicine, 2020)
BACKGROUND: As children with attention-deficit/hyperactivity disorder (ADHD) usually show psychopathological signs beyond their core symptoms (e.g. elevated scores of the dysregulation profile (DP) in 30-40%), treatments with a broader approach to self-regulation skills may be supportive. Neurofeedback (NF) may reflect such an option. Aim of the present analysis was to compare the effects of slow cortical potential (SCP) NF and θ/β NF on the DP using data from a previous trial. METHODS: Thirty children with ADHD (aged 8-12 years) and a DP score in the Strengths and Difficulties Questionnaire (SDQ-DP) ⩾ 3 were included. NF treatment consisted of one block of SCP NF and one block of θ/β NF (18 units per block) allowing an intraindividual comparison. Effects of the NF protocols were also contrasted to a control group (n = 18) that completed an attention skills training (between-group analysis). RESULTS: Regarding the SDQ-DP, SCP NF was superior to θ/β NF and the control condition. Effects of SCP NF and θ/β NF on ADHD symptom severity were not significantly different. The SDQ-DP score did not correlate with EEG-related measures previously found to be predictors for SCP NF on ADHD symptoms. CONCLUSIONS: SCP NF may reflect a more general approach to improve cognitive, emotional and behavioral self-regulation skills. If confirmed in a larger sample, the SDQ-DP score could be used as an indication criterion and contribute to the individualization of NF in ADHD. Overall, the differential effect provides further evidence for the specificity of NF effects.
EVALuna2:211386